Isolation and Cloning of ABCC9 Gene from Rasbora sarawakensis - Aimi Wahidah, Aminan (Universiti Malaysia Sarawak, (UNIMAS), 2015)
ATP Binding Cassette subfamily C member 9 (ABCC9) gene plays important role of producing the receptor of sulfonylurea 2 (SUR2). The organism used for this research is Rasbora sarawakensis which is used as vertebrate model for biomedical research. The total RNA of Rasbora sarawakensis is isolated by using TRI reagent and RT PCR is carry out to transcribe it into cDNA that later is used as a template for polymerase chain reaction (PCR). The confirmed product is then entered the cloning methods whereby the PCR product is ligated into the pGEM -T Easy Vector overnight and later is transformed by using XLI-Blue competent cell. The blue, white screening is carried out in order to grow colonies. The positive clone is picked and eluted. After that, minipreparation of plasmid DNA is conducted and the size of insert and vector were confirmed by restriction enzyme digestion of the plasmid DNA. The final sample is then sent for DNA sequencing in order to confirm the cloned gene.